Defences for Auditors' Negligent Failure to Detect Fraud - WAN, Wai Yee (Institutional Knowledge at Singapore Management University, 2008)
Comments on the two Singapore Court of Appeal decisions in PlanAssure PAC (formerly known as Patrick Lee PAC) v Gaelic Inns Pte Ltd and JSI Shipping (S) Pte Ltd v Teofoongwonglcloong (a firm) on whether auditors who have been held to be negligent for failing to detect fraud committed by their clientsÆ employees, may nevertheless raise the defence of contributory negligence on the part of their clients or claim statutory relief from liability. Reviews the policy consideration behind making available either such defence or relief from liability and whether the acts of the fraudulent employee may be attributed to the client for the purposes of determining contributory fault.